Effect of Pretreatment on the Corrosion Behavior of AHSS CP 780 Analyzed by Electrochemical Techniques - Gaona Tiburcio, Citlalli; Cabral Miramontes, José Ángel; Estupiñan López, Francisco Humberto; Lara Banda, María del Refugio; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2026)
To reduce CO2 emissions into the environment, the automotive sector uses microalloyed structural steels coated with electrophoretic paint in various components, such as the chassis, to reduce weight and increase corrosion resistance. AHSSs are coated with electrophoretic paint (E-coat). Still, to improve adhesion, they undergo a pretreatment, such as zinc phosphate or zirconium oxide. This research will analyze the effects and behavior of these coatings during corrosion on a complex-phase (CP) 780 AHSS using different electrochemical techniques, including cyclic potentiodynamic polarization (CPP), electrochemical noise (EN), and electrochemical impedance spectroscopy (EIS). The CP 780 AHSS was immersed in a 3.5 wt. % sodium chloride solution. Results show that AHSS CP 780 presented a mixed corrosion mechanism due to the heterogeneity of the surface of the zinc phosphate and zirconium oxide pretreatments. On the other hand, the samples with an E-coat paint coating and pretreatment (Zn3(PO4)2/E-coat and ZrO2/E-coat) have the lowest current densities with values of 6.44 × 10−11 1.02 × 10−9 A/cm2 and also do not show a tendency towards localized corrosion or negative hysteresis